BOOK REVIEW: Katrin Keller, Petr Mat’a, Martin Scheutz (Ed.): „Adel und Religion in der frühneuzeitlichen Habsburgermonarchie“, Böhlau Verlag Wien, 2019, ISBN 978-3-205-20390-2, p. 388 - OANCEA, Sever (Studia Universitatis Babeș-Bolyai Historia, 2019)
This volume is dedicated to Professor Thomas Winkelbauer, an exegete of the Habsburg Monarchy during the Early Modern Era. Nobles and Confession was one of the mostly addressed topics by this author during the last decades and therefore almost every researcher who approaches these topics will come across the studies carried out by the reputed Viennese scholar. It is also the case for the authors of this volume, who continue to a high extent the work of Thomas Winkelbauer.